Analysis of the Use of Formative Assessment as a Tool for Evaluating the Development tnd Learning of Young Children at RA Al-Barakah - Phadia Ananda Risky; Eva Sari; Sindy Aulia Johara; Rigita Ramadhani Kesuma; Fhara Mutia; Ampun Bantali (LPPPI Publishing, 2025)
This study aims to analyze the implementation of formative assessment at RA Al-Barakah. The research method used is descriptive qualitative research, using interviews and documentation analysis.The informants of this research were class teachers. The instruments used were interviews and documentation. The data analysis techniques used were data reduction, data presentation, and data verification. From the results of the analysis of the use of formative assessment as a tool for assessing the development and learning of early childhood at RA Al-Barakah, formative assessment and the function of formative assessment, teachers did not yet understand what formative assessment was. Factors that made it difficult for teachers to carry out formative assessment were time constraints, lack of monitoring of children, and when events were not directly recorded. The time for implementing formative assessment was carried out at the beginning of learning and continued throughout the learning process. The types of assessment used were anecdotal notes, work results, and checklist assessments.